Blockchain assisted signature and certificate based protocol for efficient data protection and transaction management in smart grids - Keyan Abdul-Aziz Mutlaq; Vincent Omollo Nyangaresi; Mohd Adib Omar; Zaid Ameen Abduljabbar; Junchao Ma; Mustafa A. Al Sibahee; Abdulla J. Y. Aldarwish; Ali Hasan Ali (PLoS ONE, 2025)
Smart grids collect real-time power consumption reports that are then forwarded to the utility service providers over the public communication channels. Compared with the traditional power grids, smart grids integrate information and communication technologies, cyber physical systems, power generation and distribution domains to enhance flexibility, efficiency, transparency and reliability of the electric power systems. However, this integration of numerous heterogeneous technologies and devices increases the attack surface. Therefore, a myriad of security techniques have been introduced based on technologies such as public key cryptosystems, blockchain, bilinear pairing and elliptic curve cryptography. However, majority of these protocols have security challenges while the others incur high complexities. Therefore, they are not ideal for some of the smart grid components such as smart meters which are resource-constrained. In this paper, a protocol that leverages on digital certificates, signatures, elliptic curve cryptography and blockchain is developed. The formal verification using Real-Or-Random (ROR) model shows that the derived session keys are secure. In addition, semantic security analysis shows that it is robust against typical smart grid attacks such as replays, forgery, privileged insider, side-channeling and impersonations. Moreover, the performance evaluation shows that our protocol achieves a 17.19% reduction in the computation complexity and a 46.15% improvement in the supported security and privacy features.